The Virtualization Cookbook for IBM Z Volume 2: Red Hat Enterprise Linux 8.2 - Parziale, Lydia (IBM Redbooks, 2021)
This IBM® Redbooks® publication is Volume 2 of a five-volume series of books entitled The Virtualization Cookbook for IBM Z®. This volume includes the following chapters: Chapter 1, "Installing Red Hat Enterprise Linux on LNXADMIN" on page 3, describes how to install and configure Red Hat Enterprise Linux onto the Linux Administration server, which performs the cloning and other tasks. Chapter 2, "Automated Red Hat Enterprise Linux installations by using Kickstart" on page 37, describes how to use Red Hat's kickstart tool to create Linux systems. This tool is fundamentally different from cloning in that an automated installation is implemented. You can try kickstart and cloning. Understand that these applications attempt to accomplish the same goal of quickly getting Linux systems up and running, and that you do not need to use both. Chapter 3, "Working with subscription-manager, yum, and DaNdiFied" on page 47, describes how the Red Hat Network works. It provides centralized management and provisioning for multiple Red Hat Enterprise Linux systems. Kickstart is an easy and fast way to provision your Linux guests in any supported Linux platform. It re-creates the operating system from the beginning by using the kickstart profile configuration file that installs the new operating system unattended. It also sets up the new guest according to the definition that was set up in the kickstart file. Usually, Linux is administered by the same team that manages Linux on all platforms. By using kickstart, you can create a basic profile that can be used in all supported platforms and customize Linux profiles, as needed. Cloning requires a better understanding of the z/VM environment and z/VM skills. It is a fast process if you enable the IBM FlashCopy® feature in advance. It clones the disks from a golden image to new disks that are used by the new Linux guest. The process can be automated by using the cloning scripts that are supplied with this book. It is recommended that you start with The Virtualization Cookbook for IBM Z Volume 1: IBM z/VM 7.2, SG24-8147 of this series because the IBM® z/VM hypervisor is the foundation (or base "layer") for installing Linux on IBM Z.